Joaquim Gomes de Souza (1829-1864): a construção de uma imagem de Souzinha - Araujo, Irene Coelho de (2012)
This thesis presents an investigation about Joaquim Gomes de Souza s life and works in order to construct the profile of the character - better known in Mathematics Brazilian s history as Souzinha (1829-1864). Thereunto, we ve discussed some of the actions that lead a person to become important to the history and how the events that made this person to become street name, name of schools, parks are recorded. We also have discussed the reasons why someone wrote books, made public tributes and monuments about this person. The theoretical-methodological approach of the French line of Discourse Analysis was adopted in the reflection on the corpus in order to approach Foucault s and Bakhtin s concepts relating them to history and linguistics, avoiding the language transparency perception and illusion of understanding several forms of possible expressions through linguistic codes. In search of ways to deal with discursive notions regarding to significance, meaning and use in history we ve studied the views of historians, philosophers and linguists as a support for the execution of the work. We reached the conclusion that Souzinha s profile is not limited to what he actually produced concerning to fantastic and perfect works. The facts, traditions, beliefs, family prestige and values present in the nineteenth century and the way biographies were written were elements that allowed his inclusion in the story